A 76 GHz oscillator by high-Q differential transmission line loaded with split ring resonator in 65-nm CMOS - Cai, Deyun (2013)
A power and area efficient CMOS oscillator by high-Q metamaterial resonator is introduced in this paper for phase noise improvement. The resonator is based on the differential transmission-line (T-line) loaded with split ring resonator (SRR), which can enhance the EM energy coupling and further improve the Q. The proposed oscillator is implemented in 65-nm CMOS process, which consumes 2.7 mA and occupies a compact core area of 480 μm × 320 μm. At the oscillation frequency (76 GHz), the measured phase noise is -108.8 dBc/Hz at 10 MHz offset and the figure-of-merit (FOM) is -182.1 dBc/Hz, which is 4 dB better than that of the standing-wave oscillator implemented on the same chip.